EXPERIENCE WITH DIASKINTEST IN THE REPUBLIC OF TATARSTAN - A. P. Alekseev; R. Kh. Fatykhova (Туберкулез и болезни лёгких)
The experience with diaskintest (DST) used to screen children for tuberculosis infection gave proof to the rationality of the technique to identify minor tuberculosis forms in children and adolescents. DST and assessment of additional risk factors for tuberculosis could detect children at high risk for the disease, who had undergone chest X-ray computed tomography before examination. The new approach to examining the children, by improving the quality of tuberculosis detection in children and adolescents, led to improved clinical pattern, the higher proportion of minor tuberculosis forms, the lower proportion of complicated tuberculosis forms, and reduced incidence of destructive tuberculosis in adolescents. However, the problem in the assessment of the activity of a tuberculous process remains in children with found minor calcinates in the intrathoracic lymph nodes because positive reactions to DST are also recorded in cases without clinical and X-ray signs of the activity of a tuberculous process.DST promotes the optimization of diagnosis of latent tuberculosis infection in children, allows identification of a group of children at the highest risk for tuberculosis among the persons with monotonous tuberculin tests, and contributes to the detection of minor tuberculosis forms.Transition to the screening of schoolchildren (over 8 years of age) and adolescents, by applying DST, makes it possible to improve the quality of diagnosis of tuberculosis infection and may be recommended for introduction in the Republic of Tatarstan as a whole.